Fundamental Retribution Error: Criminal Justice and the Social Psychology of Blame - Dripps, Donald A. (2003)
At least since the M'Naghten case of the 1840s,' Anglo- American criminal law has concerned itself closely, famously, and contentiously with the psychology of the accused. Another significant body of scholarship addresses the psychology of juries, and other valuable research has approached some of the rules of criminal evidence from the perspective of social and cognitive psychology. There has, however, yet to be a general investigation of what social cognition research might teach us about the criminal law's pervasive concern with blameworthiness. This Article undertakes that investigation. It brings research on the psychology of social cognition to bear on the decision-making processes of public officials charged with the administration of criminal justice. The psychological research suggests that these decision makers, like most other human beings, are likely to overestimate the causal significance of personal choice, and to correspondingly underestimate the causal significance of situational factors in the behavior of others. My thesis is that this observer's tendency to attribute conduct and its consequences to personality, rather than to situation, has important and disturbing implications for the theory and practice of criminal law